A Convenient and Concise Metal-Free Approach to Functionalized Bicyclic Pyrimidinones from Oxazine-2,6-diones - Shirsale, Ashwini; Patil, Yogesh; Rawal, Girish K.; Pabba, Jagadish; Berthon, Guillaume; Sonawane, Ravindra P.; Sikervar, Vikas (Synthesis, 2018)
The synthesis of previously unreported pyrazolo-pyrimidinones and isoxazolo-pyrimidinones are achieved via metal-free coupling of oxazine-2,6-diones with pyrazolidinone and isoxazolidinone, respectively. The synthesis provides easy access to a variety of novel 2-dimensional building blocks that can be derivatized to generate a range of drug- and agro-like molecules.
Keywords: isoxazolidinone; pyrazolidinone; oxazine-2,6-dione; metal-free coupling